From the Chicago School to New Developments in Urban Studies: Qualitative Methodology in a Transitional Context - Čaldarović, Ognjen (Array, 2010)
In this presentation, a link is established and docummented between the Chicago School's qualitative methodology and the new developments of research methods in urban studies